2019
DOI: 10.1111/hae.13874
|View full text |Cite
|
Sign up to set email alerts
|

Positive emotions despite substantial burden: The alchemy of haemophilia caregiving

Abstract: Introduction: Qualitative interviews when developing the haemophilia caregiver impact measure © (HCI) documented the importance of capturing the positive aspects of caregiving, not just the negative. Aim: The present study thus investigates the construct underlying the positive emotions HCI subscale and tests models proposing a more comprehensive way of thinking about this construct. Methods: Secondary analysis was implemented on longitudinal web-based survey data (n = 323) from haemophilia A or haemophilia B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…This finding is, however, consistent with our finding on the same sample that DMD caregivers did not differ from the comparison participants in resilience [25]. It is also consistent with recent work done with hemophilia caregivers suggesting that caregivers who make the best of a difficult situation tend to adopt cognitive habits characterized by both acknowledging and accepting the limitations imposed by caregiving while at the same time adopting positive-focused approaches to thinking about their caregiving experience (e.g., an awareness of the personal growth enabled by caregiving) [46]. Such a balance enables an "alchemy" of the caregiving experience, perhaps by aiding the individual to reframe challenges, possibly by increasing a 'positive balance' in their QOL [47].…”
Section: Discussionsupporting
confidence: 88%
“…This finding is, however, consistent with our finding on the same sample that DMD caregivers did not differ from the comparison participants in resilience [25]. It is also consistent with recent work done with hemophilia caregivers suggesting that caregivers who make the best of a difficult situation tend to adopt cognitive habits characterized by both acknowledging and accepting the limitations imposed by caregiving while at the same time adopting positive-focused approaches to thinking about their caregiving experience (e.g., an awareness of the personal growth enabled by caregiving) [46]. Such a balance enables an "alchemy" of the caregiving experience, perhaps by aiding the individual to reframe challenges, possibly by increasing a 'positive balance' in their QOL [47].…”
Section: Discussionsupporting
confidence: 88%
“…Their prominent focus on their brother's health and family welfare suggest core intrinsic values, such as those centered on relationships, personal well-being, and community [34]. These findings show some similarity with research on hemophilia caregivers that suggested that adopting positive ways of thinking about one's life limitations may transform the negatives of caregiving into something positive [35]. This study focused on description, and explicitly avoided interpreting the valence of such differences.…”
Section: Discussionmentioning
confidence: 68%
“…The BAI is an idiometric measure, meaning it assesses context- and circumstance-specific patient experience and meaning [ 35 ]. While data reduction techniques like principal components analysis have been used in some past research with the BAI (e.g., [ 44 , 45 ]), the component structure varies across participant population [ 35 ]. This variability is to be expected for an idiometric measure [ 35 ], but also makes it difficult to compare results across studies.…”
Section: Methodsmentioning
confidence: 99%